HOABINHIAN IN VIETNAM AND ECONOMIC ACTIVITIES FROM 20,000 TO 7,000 YEARS BP - Khac Su Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
This article studies the basic economic activities of Hoa Binh cultural inhabitants in the period of 20,000 to 7,000 years BP, including tool making, hunting, gathering, and primitive agriculture. The research results have identified a number of key economic characteristics of Hoa Binh cultural residents and evaluated the effectiveness of human methods of finding and gathering food under the fluctuations of the natural environment during the late Pleistocene to early Holocene in northern Vietnam. Little evidence directly related to cultivation and animal husbandry has been found at Hoa Binh cultural sites, so the issue of Hoa Binh agriculture is still a working hypothesis that needs to be studied further.